Effect of Different Substrates on Soil Microbial Community Structure and the Mechanisms of Reductive Soil Disinfestation - Tan, Xingyan; Liao, Hongkai; Shu, Liangzuo; Yao, Huaiying (Frontiers in Microbiology, 2019)
Reductive soil disinfestation (RSD) has recently attracted much attention owing to its effectiveness for controlling pathogens. In this study, we aimed to evaluate the effects of different C/N substrates on RSD and to explore the changes in microbial community structure during RSD treatment. The experimental set up included 10 groups, as follows: CK, without substrates; RSD treatments with alfalfa（Medicago sativa L.）[AL], maize (Zea mays Linn. Sp.) straw [MS], and rice (Oryza sativa L.) straw [RS], with three levels of addition (0.5% [L], 2% [M], and 5% [H]), yielding ALL, ALM, ALH, MSL, MSM, MSH, RSL, RSM, and RSH groups. Compared with CK, RSD treatments significantly increased the content of NH4+-N, and effectively eliminated the accumulated NO3–N in the soil. The relative abundances of organic acid producers, including Clostridium, Coprococcus, and Oxobacter, in all RSD groups were significantly higher than those in the CK by day21. Moreover, on days 21, Aspergillus and Fusarium in all RSD groups were significantly lower than those in the CK. In summary, RSD treatments clearly increased the relative abundances of organic acid generators and effectively inhibited pathogens; however, when the C/N was too low and the amount of addition too high, ammonia poisoning and rapid growth of some microorganisms (e.g., Pseudallescheria and Arthrographis) may occur.